Developing Effectivity of Student’s Speaking Skill through Questions and Answers Method at Elementary School - Karimah (Asshika: Journal of English Language Teaching and Learning, 2023)
The utilization of the question-and-answer method fosters instructor engagement with students, aligning with the self-directed curriculum. This study assesses learning outcomes across all domains, specifically cognitive, emotional, and psychomotor. The research findings indicate a rise in every domain with each cycle. Through this experimental methodology, pupils acquire the understanding that they possess the capacity to learn effectively.   Using this approach, researchers develop engaging and age-appropriate instructional sessions. The utilization of the question and response method in enhancing students' speaking skills is expected to foster cognitive function, enabling pupils to think proficiently and swiftly.